Philanthropy yet regulatory!Implementation of CSR through legislation: The Malaysian Companies Act 1965 perspectives - Abd Ghadas, Zuhairah Ariff; Hassan, Halyani (2008)
The nature of corporate social responsibility (CSR) is always regarded by companies as philanthropy. As such, many companies choose to ignore CSR by giving many excuses such as “limited fund, not enough profit, still a small business or CSR is only for public listed companies/conglomerates”. For the big companies, CSR is included in their business plan because good will and high reputation are important for the business. However, for small and medium sizes companies, CSR may not be regarded as important as it is often treated as a “welfare issue”. This is where the concern arise; many issues which CSR try to resolve are acts related to small medium sizes companies such as illegal dumping of industrial waste, open burning and improper or unsafe work place. It is highly perceived that for global changes, CSR should not be treated as philanthropy but rather as a mandatory requirement for all companies, regardless their sizes. One of the ways to do this is through legislations. With the recent amendments of Companies Act 1965, particularly in relation to directors duties to act with due diligence, it is apparent that CSR could be imposed to all companies. This paper will discuss the overall concept of CSR and the global expectation of its implementation. This paper will also analyze on how CSR could be imposed to all companies via regulations; with special reference to the Malaysian Companies Act 1965.